National building codes handbook - Hutchings, Jonathan F. (McGraw-Hill, 1998)
The fast, easy way to meet today's building codes anywhere in the USA. Your business depends on following the letter and intent of today's building codes, but it's sometimes difficult to determine exactly what that intent is. The solution? National Building Codes Handbook, by Jonathan F. Hutchings. This plain-language advisor clarifies and explains the most commonly encountered sections of the SBCCI, ICBO and BOCA codes--as well as the HUD, HVAC and other important regulations. Packed with scores of tables and diagrams that clarify practical building techniques and applications, this one-of-a-kind working tol helps you: pass inspection the first time, every time; avoid costly building code violations--and boost your reputation; clarify vague and confusing code "legalese"; discover how to follow the letter and intent of the codes in ALL your jobs; take on building jobs outside your local region with confidence; solve on-the-job problems faster and more efficiently than ever; and much more.